DINAMIKA INTEGRASI NASIONAL BANGSA INDONESIA: (Dalam Pendekatan Kerukunan Umat Beragama) - Abdul Hamid (ISTIQRA, 2016)
Diversity of religions in Indonesia are given the freedom to practice religion according to his teachings respectively. However these freedoms must be done with non-intrusive and detrimental to people of other faiths, because disruption of the relationship between followers of various religions will bring a result that can shake the unity of the nation. Various policies and programs in order to support the implementation of the development priorities of the National Defense solid, that is through the people's welfare, improve the quality of the religious and cultural resistance. Religion was very important role and strategic in the construction of National Defense solid, especially as the spiritual, moral and ethics. Religion as a value system should be understood and practiced by individuals, families, communities, and animates the life of the nation. Today there are still many people who do not have a good tolerance and integration with the many differences that exist. There are still some communities have not received such differences, the real difference as the dynamics of the life of the nation. And to keep the unity of the nation, people must regard and implement a system of social integration and national integration is a process of integration or assimilation of various socio-cultural aspects within the territorial integrity and the formation of national identity or nation that can guarantee the realization of harmony and balance in achieving a common goal as a nation